(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the rate of acute pain resolution and the improvement in cervical spine range of motion achieved through distal acupoint stimulation based on the “Huangdi Neizhen” acupoint selection method in patients with acute cervical pain due to cervical spondylosis. Materials and methods: A single-blind, randomized controlled clinical trial was conducted with two groups: distal acupuncture and electroacupuncture (62 patients per group). All patients received daily treatment for 10 consecutive days, with each session combined with at least 10 minutes of active cervical mobilization exercises. Results: After 10 days, the intervention group had a significantly higher rate of acute pain resolution compared to the control group (p < 0.05). The mean total score for cervical range of motion limitation in the intervention group was reduced to a “no limitation” level (0.74 ± 1.78 points), compared to the control group which remained at a “mild limitation” level (2.18 ± 3.03 points). The intervention group demonstrated statistically significant improvement in cervical range of motion on days 1, 2, and 6 (p < 0.05) compared to the control group. Conclusion: Distal acupoint acupuncture based on the “Huangdi Neizhen” method resulted in higher acute pain relief rates and greater improvement in cervical range of motion than electroacupuncture at local points after 10 days of treatment.